A distributed programming model for real-time industrial control - Bayne, J.S. (Control engineering practice, 1995)
The domain of industrial automation increasingly requires intelligent control, distributed real-time behaviors, and greater degrees of scalability. This has led to the creation of a new real-time, distributed, object-oriented virtual machine focused on the management of hybrid dynamic (i.e., continuous and discrete event) systems. This paper provides an outline of the virtual machine's programming model and some of its implications on the underlying execution environment.